Perancangan Sistem Informasi Helpdesk Pada Departemen ICT Menggunakan Metode FAST Di Universitas Dhyana Pura - Adnyana, Gabriel; Ardiada, I Made Dwi; Prawira Kusuma, Agus Tommy Adi (Lembaga Dongan Dosen, 2024)
Dhyana Pura University is one of the private universities in the Badung-Bali district, as an educational institution it is required to provide services to all academics, one of service for complaints about Information Technology equipment broke which is of course very important. However, what has happened so far in terms of management is that information technology equipment damage services are still experiencing several problems, namely reporting damage and handling complaints which are still recorded manually, namely using paper, so there is a risk of loss or forgetting to be followed up by technicians due to piling up files, apart from The leadership of the ICT Department also finds it difficult to monitor the activities of its technicians in handling user complaints. To overcome this problem, it is necessary to design an information system that aims to overcome this problem. In the design process, a method is needed to be used, the Framework For The Application Of System Thinking (FAST) method. FAST is a framework for various types of projects and strategies or hypotheses used for learning, developing and maintaining information systems. Because by utilizing this information system you can provide information quickly and easily. In this research, the information system design will be designed using the FAST method which consists of 7 phases, namely; Scope Definition, Problem Analysis, Requirements Analysis, Logical Design, Decision Analysis, Physical Design, and Construction and Testing, where each of the existing phases must be carried out in more detail in each scope so that the resulting output can be more accurate and more timely updates so that the resulting design can be used for development to the next stage where later this system design will be used as a reference in the website application software development process.